1998
DOI: 10.1161/01.hyp.32.5.849
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Cyclosporine A–Induced Hypertension

Abstract: Abstract-Cyclosporine A (CsA) is an immunosuppressive agent that also causes hypertension. The effect of CsA on vascular responses was determined in Sprague-Dawley rats and isolated rat aortic rings. Male rats weighing 250 to 300 g were given either CsA (25 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 ) in olive oil or vehicle by intraperitoneal injection for 7 days. CsA administration produced a 42% increase (PϽ0.001) in mean arterial pressure (MAP) that reached a plateau after 3 days. Conversely, the levels of both nitrate/nitrite, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 32 publications
5
41
0
Order By: Relevance
“…The potential role of calcineurin in eNOS regulation also may help to explain the underlying mechanism involved in the development of arterial hypertension in organ transplant recipients who are administered cyclosporin A (30). This negative side effect seems to be caused by reduced NO release from the endothelium (31,32). The molecular mechanism by which cyclosporin A affects NO release is not known but likely involves the drug acting as a selective inhibitor of the Ca 2ϩ -CaM-dependent serine/threonine-specific protein phosphatase calcineurin (27).…”
Section: Resultsmentioning
confidence: 99%
“…The potential role of calcineurin in eNOS regulation also may help to explain the underlying mechanism involved in the development of arterial hypertension in organ transplant recipients who are administered cyclosporin A (30). This negative side effect seems to be caused by reduced NO release from the endothelium (31,32). The molecular mechanism by which cyclosporin A affects NO release is not known but likely involves the drug acting as a selective inhibitor of the Ca 2ϩ -CaM-dependent serine/threonine-specific protein phosphatase calcineurin (27).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced NO production is implicated in the mechanisms not only for vasoconstriction and tubular fibrosis (Andoh et al, 1997;Assis et al, 1997) but also for extrarenal complications of CsA (Oriji and Keiser, 1998;Fiore et al, 2000). Assis et al (1997) and Zhang et al (1999) also reported that Larginine improves renal function in transplanted patients with CsA.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,24 The reduction in aortic cNOS activity might be better explained by an effect on its complex enzymatic profile rather than by a reduction of L-arginine content or consumption, since previous studies have demonstrated that L-arginine supplementation was unable to prevent CsA-induced HT. 19,25 Thus, an effect on the enzymatic cofactors of cNOS may not be excluded, as already documented in other pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Previous studies from our group, as well as from others, have shown a disequilibrium in the nitric oxide (NO)/cyclic guanosine-3=,5=-monophosphate (cGMP) system, which may contribute to the vascular hyperreactivity. 7,8 The NO system is essential to the relaxation of vascular smooth muscles cells (VSMC) and plays a pathophysiological role in reactive oxygen or nitrogen species (ROS) generation. 9 In addition, oxidative stress could also have a key role in CsA-associated cardiovascular toxicity.…”
Section: P Osttransplantation Hypertension (Ht)mentioning
confidence: 99%